Balance bike activity is better at optimizing motor components compared to bicycle and tricycle in early childhood - Yulianti, Atika; Aprilia, Dewi Nur; Prasanti , Cyrilla; Mustafidah, Lina (University of Muhammadiyah Malang, 2024)
Introduction: Riding a bicycle has become a common way for preschoolers to practice their motor skills. The purpose of this study is to evaluate how well push bikes and two- and three-wheeled pedal bicycles improve preschoolers' motor skills, including balance, agility, and leg muscle strength. Objectives: To determine how different push bikes and pedal bicycles—both two- and three-wheeled—affect preschoolers' ability to develop their motor skills. Methods: Preschoolers who participated in this study were split into three groups according to the kind of bicycle they rode: push bikes, two-wheeled pedal bicycles, and three-wheeled pedal bicycles. The study used an observational method. For a predetermined amount of time, each group used their individual bicycles for activities. Direct observation, balance, agility, and leg muscle strength assessments were all used to gather data. Results: Compared to children who rode two- and three-wheeled pedal bicycles, children who rode push bikes exhibited significantly improved balance, agility, and leg muscular strength. It has been demonstrated that push bikes are more successful in helping preschoolers develop their motor skills. Conclusions: Push bikes are more effective at improving motor components (balance, agility, and leg muscle strength) in preschool children bicycle and tricycle. As a result, push bikes are a superior option for helping preschoolers develop their motor skills.